Unveiling Figurative Meaning: In-Depth Investigation into Taylor Swift’s Song ‘Cruel Summer’ - Nabila Mahdafiqya; Anita Dewi Ekawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Taylor Swift's works have been known to have lyrics that are rich in meaning and have hidden figurative meanings, therefore many listeners have difficulty understanding the meaning in the lyrics of her songs and some even interpret them incorrectly. This research is to uncover the hidden figurative meanings in Taylor Swift's "Cruel Summer" lyrics and explore the use of figurative language and emotional expressions to convey deeper meanings. A qualitative descriptive method was used to analyze the song lyrics, with an approach based on Perrine's (1969) theory of figurative language. Data collection is based on observation of the lyrics of the song 'Cruel Summer'. The results of the analysis show that there are 19 figurative data with 7 different types of figurative language: 2 similes (10.53%), 8 metaphors (42.11%), 2 personifications (10.53%), 1 synecdoche (5.26%), 3 symbols (15.79%), 2 hyperboles (10.53%), and 1 irony (5.26%). The dominant figurative language in the lyrics of "Cruel Summer" is a metaphor with the largest percentage (42.11%). Taylor Swift uses metaphors to convey her message directly using other terms with more beautiful language.